Analyis on the vascular epiphytes of tree ferns in a montane rain forest in Costa Rica - Jens Bittner; Javier Trejos Zelaya (Revista de Matemática: Teoría y Aplicaciones, 2009)
The relationships between epiphytes and host specifity are known. We investigated the relation between specific epiphytes and tree fern trunks. Only some epiphytes are frequent or very frequent on tree ferns. Most of the epiphyte species are unspecific on these trunks. Blechnum fragile are the only found exclusively on tree ferns. We also observed different epiphyte communities dependent on the tree fern species and the morphology of the tree trunk.